2008
DOI: 10.1017/s1368980008002346
|View full text |Cite
|
Sign up to set email alerts
|

Use of folic acid supplements, particularly by low-income and young women: a series of systematic reviews to inform public health policy in the UK

Abstract: Objective: To provide a basis for making recommendations on the potential to improve use of folic acid supplements in the UK, particularly among low-income and young women. Design: Systematic reviews of relevant research from 1989 to May 2006 in Europe, the USA, Canada, Australia and New Zealand. Results: Twenty-six systematic reviews and/or meta-analyses were identified from the wider public health literature, and eighteen studies on the effectiveness of preconception interventions were included. Ninety studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 106 publications
9
71
1
Order By: Relevance
“…However, a systematic review showed that study quality was often poor. Most studies were small and were conducted late in pregnancy or even after delivery, which led to a high risk of recall bias, and most studies only used univariable analyses (18) . The most recent data on folic acid use in the Netherlands derive from studies in 2003-2004 and 1995-2005.…”
mentioning
confidence: 99%
“…However, a systematic review showed that study quality was often poor. Most studies were small and were conducted late in pregnancy or even after delivery, which led to a high risk of recall bias, and most studies only used univariable analyses (18) . The most recent data on folic acid use in the Netherlands derive from studies in 2003-2004 and 1995-2005.…”
mentioning
confidence: 99%
“…Failure of contraceptive methods is one reason for an unplanned pregnancy. Secondly, unplanned pregnancy is one predictor of low compliance to the FA recommendation as reviewed by Ray et al (2004) and Stockley & Lund (2008). Combining OC with folate would result in a protective maternal folate status for OC users being advantageous to those conceiving under OC therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Less than recommended or no FA supplementation was associated with unplanned pregnancy (McGuire et al, 2010). As indicated in the systematic reviews of Ray et al (2004) and Stockley & Lund (2008), unintended pregnancy is the most important factor for lack of compliance with the recommendations. …”
Section: Planned and Unplanned Pregnancymentioning
confidence: 99%
“…44 Nevertheless, the increased rate of FA consumption did not parallel the efforts spent to implement and establish such programs. Stockley and Lund 45 conducted a comprehensive review of published literature from 1989 to 2006 on the effectiveness of various interventions to improve the periconceptional use of FA. They concluded that even highquality campaigns that result in an increase in the use of FA would have a limited impact, as more than half of the women are poorly compliant, and programs often will not reach unplanned pregnancies.…”
Section: Predictors Of Suboptimal Use Of Famentioning
confidence: 99%
“…Similar results were obtained from a systematic review by Chivu et al 46 where the average usage of FA was less than 25% following diverse interventions used to increase FA intake. 45,46 Furthermore, Botto et al 47 in a retrospective cohort study that included 8,636 cases of anencephaly or spina bifida reported by birth registries in 13 areas in Europe and Israel, identified that recommendations and broadcasting information alone did not have a measurable effect on the prevalence of NTD. 45,47 National integrated health promotion programs embracing information on patterns and predictors of FA consumption and incorporating public and health professional's education to implement environmental, behavioral, and social policy changes could be an effective way to develop a successful program.…”
Section: Predictors Of Suboptimal Use Of Famentioning
confidence: 99%